The tadpole of Scinax melanodactylus (Lourenço, Luna & Pombal Jr, 2014) (Amphibia, Anura, Hylidae) - Abreu, Rafael Oliveira De; Napoli, Marcelo Felgueiras; Trevisan, Camila Costa; Camardelli, Milena; Dória, Thais Andrade Ferreira; Silva, Lucas Menezes (Zootaxa, 2015)
Scinax melanodactylus is a small treefrog distributed within the Tropical Atlantic morphoclimatic domain (see Ab’Sáber 1977 for South American morphoclimatic domains), from northern Espírito Santo state to Sergipe state in Brazil (Lourenço et al. 2014). The species is usually found inhabiting herbaceous and shrubby xerophytic vegetation (e.g. terrestrial tank-bromeliads) from sandy plains of beach ridges known in Brazil as Restingas (see Rocha et al. 2007 for a Restinga definition), and also the edge of forest areas with temporary ponds and/or permanent lakes and streams near these environments (Bastazini et al. 2007, as Scinax agilis; Lourenço et al. 2014). Scinax melanodactylus is currently placed in the S. catharinae species group (Lourenço et al. 2014), which in turn is included in the S. catharinae clade (sensu Faivovich et al. 2005). The S. catharinae clade is currently comprised of 46 species, 33 placed in the catharinae group and 13 in the perpusillus group (Faivovich et al. 2010, Silva & Alves-da-Silva 2011, Lourenço et al. 2014, Frost 2015). From these, 32 species have tadpoles with external morphology and oral disc formerly described. Here, we describe the external morphology, oral disc and color patterns of the previously unknown tadpole of S. melanodactylus.